Isolation and characterization of GA 20-oxidase gene from sago palm (Metroxylan sagu) - Bala, Jamel (University Malaysia Sarawak, UNIMAS, 2013)
GA 20-oxidase is one of the enzymes that are involved in the production of gibberellins. Gibberellins are plant hormones that are involved in controlling seed germination, stem elongation, leaf expansion, flower induction and development and growth of seed and fruit. Based on previously published conserved amino acid sequences of the plant GA 20- oxidase cDNA clones, oligonucleotide primers were used to amplify GA 20-oxidase gene from genomic DNA of sago palm. PCR amplification using this primer produced a single band with the estimated size of 500 bp in length. BLAST analysis has shown that this fragment was homologous with GA 20-oxidase gene. Based on the sequence obtained, several sets of gene specific primers were constructed and used to amplify the full-length gene both from genomic DNA and cDNA. The total size of GA20-oxidase gene obtained from genomic DNA and cDNA was 1332 and 1161 bp respectively. Comparison between genomic and cDNA sequence showed that, the GA 20-oxidase gene is comprised of two introns and three exons. In order to study the heterologous expression, GA 20-oxidase gene was cloned into pPCR-Script Amp SK (+) vector in sense direction and in correct reading frame, and was then transformed into Escherichia coli (E. coli). Protein was then extracted from E. coli and the fusion protein was analysed using western blot analysis. Heterologous expression was compared with endogenous GA 20-oxidase of sago palm. Expression activity was detected with polyclonal antibody which was induced and produced in a rabbit using short peptide sequence of sago GA 20-oxidase. Western hybridization analysis showed the presence of an intact 32 kDa band, for both crude protein samples obtained from sago tissue and E. coli containing sense GA 20-oxidase gene. No band was observed for protein extracted from negative control sample. This study indicated that the endogenous and heterologous products might be encoded by the same gene, GA 20-oxidase.